Trump’s Protectionism Threatens Indonesian Exports: Predicting the Impact on National Economic Resilience - Dewi, Ni Luh Yulyana; Fatmawati, Endang; Hasibuan, Masnilam; Mayasari, Yane; Marbun, Frederic Kornelius; Kuswandi, Dadi (GoAcademica Research & Publishing, 2024)
This study investigates the potential impacts of President Trump’s protectionist policies on Indonesia’s export sector, with a particular focus on national economic resilience. The protectionist stance, which includes elevated tariffs and trade restrictions, has historically influenced global trade dynamics, affecting emerging markets like Indonesia. By conducting an extensive literature review, this paper aims to analyze previous instances of U.S. protectionist policies, particularly under Trump’s administration, and their repercussions on trade partners. The study examines the vulnerability of Indonesia’s key export sectors textiles, electronics, and agriculture and discusses the possible economic consequences, such as reduced GDP growth, increased trade imbalance, and employment risks. Findings from this review reveal that heightened U.S. protectionism could significantly disrupt Indonesia’s export flows, challenging the country’s economic stability. Policy implications underscore the need for Indonesia to diversify its export markets, enhance competitive capacities, and explore alternative economic strategies. This paper provides a comprehensive perspective on the indirect effects of U.S. economic policies on Indonesia, contributing valuable insights to policymakers and stakeholders preparing for future trade uncertainties.